2020
DOI: 10.21203/rs.3.rs-91495/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Cognitive and Neuroimaging Profiles in Later-Life Attention Deficit/Hyperactivity Disorder and Mild Cognitive Impairment

Abstract: Background: Attention deficit/hyperactivity disorder (ADHD) is increasingly being recognized in adults and older adults. Some of its behavioral features (e.g., distractibility, forgetfulness, impulsivity) may resemble those of mild cognitive impairment (MCI), which contributes to diagnostic uncertainty in later life. The present study aimed to systematically compare ADHD and MCI on measures of cognition and structural neuroimaging to clarify the extent of their overlap (i.e., cognitive features of ADHD that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has been presumed that poor memory strategy selection in those individuals due to a disrupted phonological loop may lead to inefficient encoding of the material to be learned. With the deficient conversion of verbal stimuli into memory, performances in tasks involving retrieval of information both spontaneously and in response to verbal cues predictably fall below the average levels ( 39 , 41 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been presumed that poor memory strategy selection in those individuals due to a disrupted phonological loop may lead to inefficient encoding of the material to be learned. With the deficient conversion of verbal stimuli into memory, performances in tasks involving retrieval of information both spontaneously and in response to verbal cues predictably fall below the average levels ( 39 , 41 ).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, scores in executive function tasks were comparable between ADHD and MCI groups. Accordingly, previous reports suggested that severity of frontal-executive impairments in ADHD, whether inherent of the disorder or exacerbated by age-related cognitive decline, might be compatible with subtle, but measurable difficulties to perform everyday life activities, which might mimic MCI presentation ( 41 , 42 ). Longitudinal investigation of executive control in this diagnostic group may clarify about the contribution of aging to cognitive load and disability in ADHD.…”
Section: Discussionmentioning
confidence: 98%